The puzzle of modern economics science or ideology - Backhouse, Roger 1951- (Cambridge University Press, 2010)
Does economics hold the key to everything or does the recent financial crisis show that it has failed? This book provides an assessment of modern economics that cuts through the confusion and controversy on this question. Case studies of the creation of new markets, the Russian transition to capitalism, globalization, and money and finance establish that economics has been very successful where problems have been well defined and where the world can be changed to fit the theory, but that it has been less successful in tackling bigger problems. The book then offers a historical perspective on how economists have, since the Second World War, tried to make their subject scientific. It explores the evolving relationship between science and ideology and investigates the place of heterodoxy and dissent within the discipline